MANUFACTURE OF COOKING OIL CONTENT DRAIN CONTROL DEVICE IN OILY FOODS USING THE ESP32-BASED AND FUZZY LOGIC METHOD - Nadia, Ninda Syafa Ainun; Astawa, I Gede Puja; Budikarso, Anang; Aswoyo, Budi; Anisah, Ida; Nadziroh, Faridatun (Transmisi: Jurnal Ilmiah Teknik Elektro, 2024)
Cooking oil is an essential commodity in everyday life in Indonesia, with palm oil consumption reaching 18.5 million tons in 2021, according to the Indonesian Palm Oil Association (GAPKI). High levels of consumption can potentially increase the risk of health problems. To reduce oil consumption, slicing of food is required. However, this process is often done manually, which is less effective. Therefore, this study proposes the development of an automatic control device using the YF-S201 flow sensor, TCS3200 color sensor, and DS18B20 temperature sensor, which then processes the data using the fuzzy logic method. Data processing and monitoring are performed using ESP32, displaying results on the LCD and website. Data is stored in a MySQL database. The test was conducted on shrimp crackers weighing 0.5kg for 1 minute 25 seconds. This control device is hoped to help households, traders, and MSMEs as an effective and efficient solution. The characteristics of the three sensors, namely the TCS3200 colour sensor, flow sensor YF-S201, and temperature sensor DS18B20, it was found that the sensor had worked well as expected, with a maximum error percentage of 0.91%. In one of the tests to drain oil on oily crackers, the oil flow was detected to be 0.07 litres/minute of oil flowing out of the oil filter.